Parasitismo natural de ovos do curuquerê-do-algodoeiro por Trichogramma pretiosum em diferentes estágios fenológicos de variedades de algodoeiros em Ipameri, GO - Costa, Lilian Lucia [UNESP]; Funichello, Marina [UNESP]; Busoli, Antonio Carlos [UNESP] (Universidade Federal de Uberlândia (UFU), 2010)
The cotton can be damaged by many pests, standing out among them cotton leafworm, responsible for major losses in production, if not controlled properly. A group of natural enemies is the most studied of the family Trichogrammatidae, mainly species of the genus Trichogramma, because of its importance in biological control at the initial stage of development of their hosts. In order to study the natural egg parasitism of Alabama argillacea (Hubner, 1818) (Lepidoptera: Noctuidae) by Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae) in different phenological stages of transgenic and conventional varieties of cotton (Gossypium hirsutum L.) in the region of Ipameri, GO, it was carried out this experiment from december 2007 to april 2008, in the UEG, State of Goias. The experimental design was in randomized blocks with five treatments consisting of the conventional varieties DeltaOPAL, FMX 966, FMX 993, FMX 910 and NuOPAL transgenic variety, in four replications. In the beginning of oviposition of the A. argillacea it was started the 27 old days plant and the parasitism increased as the availability of eggs of the host, regardless of variety. It was found that the varieties over the vegetative cycle did not show statistical differences on the preference for oviposition by the moth neither on the parasitism. The level of parasitism of eggs of A. argillacea by T. pretiosum varied depending on the density of eggs on plants, not in terms of varieties and phenological stages.

Com o objetivo de estudar o parasitismo natural de ovos de Alabama argillacea por Trichogramma pretiosum em diferentes estágios fenológicos de variedades convencionais e transgênica na região de Ipameri, GO foi realizado um experimento no período de dezembro de 2007 à abril de 2008, na UEG, Universidade Estadual de Goiás. O delineamento experimental foi blocos ao acaso, com cinco tratamentos constituídos pelas variedades convencionais DeltaOPAL, FMX 966, FMX 993; FMX 910 e a transgênica NuOPAL em quatro repetições. A partir do início da oviposição da praga, aos 27 dias após emergência das plantas, já houve o estabelecimento da população do parasitóide, aumentando o parasitismo dos ovos de A. argillacea por T. pretiosum à medida que aumentou também a disponibilidade de ovos do hospedeiro, independente da variedade. Considerando as variedades ao longo do ciclo do algodoeiro, verificou-se que as variedades não apresentaram diferenças estatísticas em relação à preferência de oviposição pela mariposa e nem em relação ao parasitismo. O nível de parasitismo de ovos de A. argillacea por T. pretiosum variou em função da densidade de ovos nas plantas, e não em função das variedades e fases fenológicas.
Natural egg parasitism of cotton leafworm by Trichogramma pretiosum (Hymenoptera: trichogrammatidae) in different phenological stages of cotton varieties in Ipameri, GO
Keywords: Gossypium hirsutum; Natural Biological Control; Alabama argillacea